THEORETICAL AND METHODOLOGICAL BASIS OF FORMATION OF INVESTMENT RESOURCES AND ANALYSIS OF INTERNATIONAL EXPERIENCE - Asadbek Mustafoyev (Ecominds Press, 2026)
This article studies theoretical concepts and modern international models of investment resource formation in the context of improving the national economy. In particular, the impact of neoclassical and Keynesian approaches on investment activity, as well as the specific features of the Anglo-Saxon, Continental and East Asian models, are compared and analyzed. As a result of the study, scientific conclusions are formulated on the diversification of investment resources for emerging markets.
Keywords: Investment resources, capital accumulation, savings rate, multiplier effect, financial markets, institutional environment.